Psychometric properties of handwriting analysis – review of researches - Górska, Zuzanna (Studia Psychologica: Theoria et praxis, 2007)
The paper is a survey of research aimed at establishing the validity and reliability of graphology as a projective technique used in analysing personality and temperament. The focus is mainly on research conducted in the last two decades by psychologists, but also criminologists (in the aspect of handwriting’s stability). Apart from presenting empirical evidence confirming or contradicting psychometric properties of graphology, the paper also includes an evaluation of methodology used in the different studies.